2007
DOI: 10.1111/j.1464-410x.2007.07021.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic activation of phasic activity in the isolated bladder: possible evidence for M3‐ and M2‐dependent components of a motor/sensory system

Abstract: OBJECTIVES To analyse pressure changes induced by muscarinic agonists on the isolated bladder in order to examine whether there are different responses representing different components of a motor/sensory system within the bladder wall. MATERIALS AND METHODS Whole isolated bladders from 19 female guinea‐pigs (280–400 g) were used. A cannula was inserted into the urethra to monitor intravesical pressure and the bladder was suspended in a heated chamber containing carboxygenated physiological solution at 33–36 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
5
24
0
Order By: Relevance
“…Our unpublished observation also suggested that the M 3 subtype has a primary role in the contraction of guinea pig UBSM tissues in response to cholinergic stimulation; methacholine-induced contraction was competitively inhibited by methoctramine and solifenacin with their pA 2 values corresponding to M 3 subtype rather than M 2 . The primary role of the M 3 subtype in guinea pig UBSM tissue contraction is also supported by reports from different research groups [14,15] . The possible underlying mechanisms of M 3 subtype-mediated contraction in UBSM tissues include Ca 2+ mobilization, which is triggered through phospholipase C and is postulated to be enhanced in the smooth muscle contractions that are mediated through other G q -protein-coupled receptors [16,17] .…”
Section: Discussionsupporting
confidence: 58%
“…Our unpublished observation also suggested that the M 3 subtype has a primary role in the contraction of guinea pig UBSM tissues in response to cholinergic stimulation; methacholine-induced contraction was competitively inhibited by methoctramine and solifenacin with their pA 2 values corresponding to M 3 subtype rather than M 2 . The primary role of the M 3 subtype in guinea pig UBSM tissue contraction is also supported by reports from different research groups [14,15] . The possible underlying mechanisms of M 3 subtype-mediated contraction in UBSM tissues include Ca 2+ mobilization, which is triggered through phospholipase C and is postulated to be enhanced in the smooth muscle contractions that are mediated through other G q -protein-coupled receptors [16,17] .…”
Section: Discussionsupporting
confidence: 58%
“…This agonist is more selective for muscarinic receptors compared to carbachol with a greater selectivity for the M2 than the M3 receptor . However, similar responses of both agonists have been described before in isolated bladder preparations (Finney et al, 2007;Gillespie et al, 2015c).…”
Section: Discussionsupporting
confidence: 57%
“…Previous guinea pig studies have shown that exposure of the whole isolated bladder to arecaidine, resulted in complex transient rises in intravesical pressure Finney et al, 2007). In the present study, comparisons were made between the arecaidine-induced responses in isolated rat and guinea pig whole bladder preparations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The physiological relevance of this phasic activity is not clear, but it may play a role in mediating the tone of the bladder and relaying sensory afferent information [2]. A population of cells similar to interstitial cells of Cajal (ICCs) in the gut have been found in the bladder lamina propria and detrusor layers [3] and it is suggested that these cells play a role in modulating the phasic activity of the detrusor [4].…”
Section: Introductionmentioning
confidence: 99%